Evaluation of center-line extraction algorithms in quantitative coronary angiography. - Greenspan, H. (IEEE Transactions on medical imaging)
Objective testing of centerline extraction accuracy in quantitative coronary angiography (QCA) algorithms is a very difficult task. Standard tools for this task are not yet available. The authors present a simulation tool that generates synthetic angiographic images of a single coronary artery with predetermined centerline and diameter function. This simulation tool was used creating a library of images for the objective comparison and evaluation of QCA algorithms. This technique also provides the means for understanding the relationship between the algorithms performance and limitations and the vessel's geometrical parameters. In this paper, two algorithms are evaluated and the results are presented.